Internet connectivity disruption in Gambia (Gambia) - Voidly (2026)
CRITICAL severity disruption detected in Gambia. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: GM-2026-0003
Keywords: internet disruption; GM; disruption; critical